Design of Application Reservations, Check-In, And Check-Out At Hotel Halogen Juanda - Setyahadi, Muhammad Fakhrizal; Sulistiowati, Sulistiowati; Lemantara, Julianto (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2018)
PT Cahaya Halogen Hotel is a company engaged in hospitality. Halogen Hotel has cooperated with several third parties such as Traveloka and Agoda. One of the main business processes in the Hotel is when guests make reservations, payments, Check-in, Check-out, until the reservation report. Along with the increasing number of reservations, there are some obstacles, such as errors in recording reservations that are not in accordance with guest requests. The unavailability of a reservation system for rooms is also an obstacle for guests who want to rent a room. From the above problems, an online-based reservation, check-in, and check-out application is built that can help and facilitate guests in making reservations until Check-out. For the hotel can help manage the process from reservation, check-in, check-out, to report. Based on the results of the trial with the black box testing method in the application that has been made, the application can store data on reservation, check-in, and check-out requirements such as room type, available services, check-in and check-out history, payment on during reservation and reservation report. The benefits obtained are the Halogen Hotel will be easier in serving guest reservations that will stay overnight and minimize recording errors in the Front Office in recording guest data, and can help convey information with media publications about the hotel to guests who will stay.